2001
DOI: 10.1016/s0020-7292(01)00368-x
|View full text |Cite
|
Sign up to set email alerts
|

Care for adolescent pregnancy and childbirth

Abstract: The rise in adolescent pregnancy in the 20th century has been influenced by declining age at menarche, increased schooling, delay of marriage, inadequate contraception and poverty. The main problems are preterm labor, hypertensive disease, anemia, more severe forms of malaria, obstructed labor in very young girls in some regions, poor maternal nutrition and poor breastfeeding. In many regions HIV infection is an important problem. The infants of adolescent mothers are more prone to low birth weight and increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
1
8

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 44 publications
6
41
1
8
Order By: Relevance
“…Specifically, our results highlight the need to develop early preventive interventions if there is a likelihood of early sexual intercourse, as this may represent a longer exposure to the potential risk of pregnancy (Araújo Pedrosa, 2009;Coley & Chase-Lansdale, 1998;Treffers et al, 2001;Valle et al, 2005). Regarding the characteristics of younger adolescents, school appears to be a preferential preventive context when both they and their partners are students.…”
Section: Relationship Characteristicsmentioning
confidence: 75%
See 1 more Smart Citation
“…Specifically, our results highlight the need to develop early preventive interventions if there is a likelihood of early sexual intercourse, as this may represent a longer exposure to the potential risk of pregnancy (Araújo Pedrosa, 2009;Coley & Chase-Lansdale, 1998;Treffers et al, 2001;Valle et al, 2005). Regarding the characteristics of younger adolescents, school appears to be a preferential preventive context when both they and their partners are students.…”
Section: Relationship Characteristicsmentioning
confidence: 75%
“…However, other variables should be considered in interventions to prevent unplanned pregnancy (Phipps et al, 2008). Adolescents in the youngest age group reported earlier age at menarche and at first sexual intercourse and lower gynaecological age, characteristics that distinguish them from the other groups and that should not be ignored given younger adolescents' longer exposure to the potential risk of pregnancy (Araújo Pedrosa, 2009;Treffers, Olukoya, Ferguson, & Liljestrand, 2001;Valle, Torgersen, Røysamb, Klepp, & Thelle, 2005). On the other hand, they have less knowledge about sexual health (Leppälahti et al, 2012) and lower cognitive ability, which decreases their competence in contraceptive decision-making (Commendador, 2007) and explains the non-use or incorrect use of contraception (Wang & Chiou, 2008).…”
Section: Relationship Characteristicsmentioning
confidence: 99%
“…Nevertheless some studies highlighted controversies considering the teenage pregnancy as single risk factors for the low weight at birth (Treffers, Olukoya, Ferguson, & Liljestrand, 2001;Suzuki et al, 2007;Amorim, Lima, Lopes, Araujo, Silva, César, & Melo (2009);Yazlle et al, 2009;Oliveira et al, 2010). However, regarding the NB prematurity, data from developed and developing countries showed that teenage mothers are at the highest risk for such event, when compared to mothers above 20 years.…”
Section: Discussionmentioning
confidence: 99%
“…It is also somewhat expected for them to feel depressed and lonely since they were isolated from families and friends. As such, it is crucial to assist the young women on what options are available to them and how to disclose their condition to family members (Hayward, 2011;Treffers et al, 2001). A lot of encouragement and motivation are also needed to give them hope for the future.…”
Section: Discussionmentioning
confidence: 99%